2016
DOI: 10.1111/asj.12734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary heme iron and exercise training on abdominal fat accumulation and lipid metabolism in high‐fat diet‐fed mice

Abstract: Animal by-products can be recycled and used as sources of essential nutrients. Water-soluble heme iron (WSHI), a functional food additive for supplementing iron, is produced by processing animal blood. In this study, we investigated the effects of dietary supplementation of 3% WSHI and exercise training for 4 weeks on the accumulation of abdominal fat and lipid metabolism in mice fed high-fat diet. Exercise-trained mice had significantly less perirenal adipose tissue, whereas WSHI-fed mice tended to have less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Previous studies reported that ex vivo and in vitro treatment of murine adipocytes with iron increased glycerol release (Rumberger et al 2004;Chirumbolo et al 2015), suggesting the possibility that iron may directly or indirectly activate ATGL and/or HSL, the two primary enzymes catalyzing triglyceride hydrolysis (i.e., lipolysis). Gene expression of HSL was recently reported to be significantly increased (and the increase in ATGL expression was nearly statistically significant) in mice after four weeks of dietary iron supplementation (Katsumura et al 2017) but to our knowledge, the influence of iron on lipase protein activation/abundance has not been previously examined. Our findings that total protein abundance of both HSL and ATGL and the ratio of p-HSL ser660 :HSL were significantly greater in High-ferritin vs. Low-ferritin suggest that iron may increase lipase protein abundance and activation.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies reported that ex vivo and in vitro treatment of murine adipocytes with iron increased glycerol release (Rumberger et al 2004;Chirumbolo et al 2015), suggesting the possibility that iron may directly or indirectly activate ATGL and/or HSL, the two primary enzymes catalyzing triglyceride hydrolysis (i.e., lipolysis). Gene expression of HSL was recently reported to be significantly increased (and the increase in ATGL expression was nearly statistically significant) in mice after four weeks of dietary iron supplementation (Katsumura et al 2017) but to our knowledge, the influence of iron on lipase protein activation/abundance has not been previously examined. Our findings that total protein abundance of both HSL and ATGL and the ratio of p-HSL ser660 :HSL were significantly greater in High-ferritin vs. Low-ferritin suggest that iron may increase lipase protein abundance and activation.…”
Section: Discussionmentioning
confidence: 85%
“…The final hydrolysis of MG to glycerol and FFA is catalysed by monoacylglycerol lipase (MGL) (49,52). Increased expression of the Lipe gene was observed in the epididymal adipose tissue of mice with dietary haem-induced iron loading (53). Consistent with this finding, carbonyl iron-loaded mice have elevated Atgl and Lipe protein with a greater proportion of both phosphorylated in adipose tissue (54).…”
Section: Lipid Uptake and Traffickingmentioning
confidence: 63%
“…lipolysis). Gene expression of HSL was recently reported to be significantly increased (and the increase in ATGL expression was almost statistically significant) in mice after 4 weeks of dietary iron supplementation (Katsumura et al, 2017), but to our knowledge, the influence of iron on lipase protein activation/abundance has not been examined previously. Our findings that total protein abundance of both HSL and ATGL and the ratio of p-HSL ser660 to HSL were significantly greater in the High-ferritin versus Low-ferritin group suggest that iron might increase lipase protein abundance and activation.…”
Section: Discussionmentioning
confidence: 86%